Pharmacogenetics of Dolutegravir Plasma Exposure Among Southern Africans With Human Immunodeficiency Virus . (4th May 2022) - Cindi, Zinhle; Kawuma, Aida N; Maartens, Gary; Bradford, Yuki; Venter, Francois; Sokhela, Simiso; Chandiwana, Nomathemba; Wasmann, Roeland E; Denti, Paolo; Wiesner, Lubbe; Ritchie, Marylyn D; Haas, David W; et al.
Abstract: Background: Dolutegravir is a component of preferred antiretroviral therapy (ART) regimens. We characterized the pharmacogenetics of dolutegravir exposure after ART initiation in the ADVANCE trial in South Africa. Methods: Genome-wide genotyping followed by imputation was performed. We developed a population pharmacokinetic model for dolutegravir using nonlinear mixed-effects modeling. Linear regression models examined associations with unexplained variability in dolutegravir area under the concentration-time curve (AUCVAR ). Results: Genetic associations were evaluable in 284 individuals. Of 9 polymorphisms previously associated with dolutegravir pharmacokinetics, the lowest P value with AUCVAR was UGT1A1 rs887829 ( P = 1.8 × 10 −4 ), which was also associated with log10 bilirubin ( P = 8.6 × 10 −13 ). After adjusting for rs887829, AUCVAR was independently associated with rs28899168 in the UGT1A locus ( P = .02), as were bilirubin concentrations ( P = 7.7 × 10 −8 ). In the population pharmacokinetic model, rs887829 T/T and C/T were associated with 25.9% and 10.8% decreases in dolutegravir clearance, respectively, compared with C/C. The lowest P value for AUCVAR genome-wide was CAMKMT rs343942 ( P = 2.4 × 10 −7 ). Conclusions: In South Africa, rs887829 and rs28899168 in the UGT1A locus were independently associated with dolutegravir AUCVAR . The novel rs28899168 association warrants replication. This study enhances understanding of dolutegravir pharmacogenetics in Africa. Abstract : Steady-state dolutegravir concentration-time data from Southern Africans were analyzed using nonlinear mixed effects. We characterized genetic associations with unexplained variability in dolutegravir area under the concentration-time curve (AUCVAR ). UGT1A1 rs887829 and UGT1A rs28899168 were independently associated with dolutegravir AUCVAR .